Implementation of marketing concepts into supply chain management - Krykavskyy, E. V.; Pokhylchenko, E. А. (Видавництво Львівської політехніки, 2014)
The integration of strategic marketing approaches, particularly, in the sales unit of the supply chain, into other functional areas such as logistics and financе, in order to minimize target conflicts and achieve competitive advantages is substantiated in the article. The use of marketing – logistics approach to supply chain management is actualized. A critical review of modern marketing concepts is presented. The necessity of integrating the concept of Supply Chain Management, on the one hand, with the concept of Customer Relationship Management, which will facilitate interconnection of financial, marketing and logistics purposes and will help to move away from the traditional dilemma “elasticity contra efficiency”, and, on the other hand, with the concept of Supplier relationship management, which will control the entire supply cycle from the strategic planning to the end user sale is substantiated. The effect of such integration on the key processes and the management effectiveness indicators of the total supply chain is identified.
Keywords: supply chain; integration of logistics; finance and marketing; relationship marketing; experience marketing; CSR; CRM; SCM